Effectiveness of Supply Management Using Kanban System in Hospital Pharmacy Logistics: A Case Study - Yuniar, Cinthya Ratna; Wida Riana; Ulfa Nur Maa'idah; Erna Agung Rakhmawati (Airlangga Journal of Innovation Management, 2023)
The aims of this research are, first to determine the stock profile of medical consumables before and after the implementation of Kanban system, and second to analysis the effectiveness inventory management of Kanban application. The research method uses descriptive quantitative by comparing the pre-experimental and post-experimental averages. An experiment was conducted to apply the Kanban system to pharmaceutical logistics at a hospital in Ponorogo for two months. Analysis using the FSN method based on TOR, ROP method, Safety Stock method followed by the implementation of the Kanban system. The results obtained are the average pre-Kanban purchase is 6715.7 and post-Kanban is 2232.8. The average ending inventory before Kanban is 8638.6 and after Kanban is 1656.2. The results of the paired t test yield a significant value for purchases of 0.168, which means that there are significant differences in pre-Kanban and post-Kanban purchases. The percentage of effectiveness tested with an N Gain score of 49.362% for purchases and for final stock of 47.655% shows that it is still in the less effective category. The benefit of this research is that in theory it provides an overview of the method for testing the effectiveness of kanban implementation, in practice it provides an overview of Kanban implementation.